Preditor de Smith Filtrato Simplificado com Ação Feedforward - Nascimento Júnior, José Nogueira do (2022)
This work proposes a new control structure for dead-time systems based on the simplified filtered Smith predictor (SFSP), which uses a feedforward action. The proposed strategy is based on a stable implementation tuning methodology and makes use of an auxiliary filter to obtain the controller parameters more directly in relation to the traditional SFSP topology. The structure preserves the good robustness and noise attenuation properties of SFSP, while improving its measurable disturbance rejection performance through the feedforward action. The evaluation of the proposed methodology is carried out through simulation results which present better performance indexes when compared to other recent strategies in the literature. In order to validate the implementation of the proposal, the controller was implemented in a prototype of a neonatal incubator to control the temperature of its dome, where a better perturbation rejection was obtained compared to the classical structure of the SFSP.